2017
DOI: 10.5811/westjem.2016.11.32273
|View full text |Cite
|
Sign up to set email alerts
|

A Patient-Centered Emergency Department Management Strategy for Sickle-Cell Disease Super-Utilizers

Abstract: IntroductionA subpopulation of sickle-cell disease patients, termed super-utilizers, presents frequently to emergency departments (EDs) for vaso-occlusive events and may consume disproportionate resources without broader health benefit. To address the healthcare needs of this vulnerable patient population, we piloted a multidisciplinary intervention seeking to create and use individualized patient care plans that alter utilization through coordinated care. Our goals were to assess feasibility primarily, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…However, most studies on ED use tend to report on overall utilization in the SCD population with a focus on superutilizers and ED visit reduction approaches. 4,5,7,11,19,[28][29][30][31][32][33][34][35] Similar to some of these studies, our study also found that the majority of participants were not high ED utilizers. 11 However, the stigma and pervasive negative ED experiences have been empirically noted across our study and several others.…”
Section: Discussionsupporting
confidence: 89%
“…However, most studies on ED use tend to report on overall utilization in the SCD population with a focus on superutilizers and ED visit reduction approaches. 4,5,7,11,19,[28][29][30][31][32][33][34][35] Similar to some of these studies, our study also found that the majority of participants were not high ED utilizers. 11 However, the stigma and pervasive negative ED experiences have been empirically noted across our study and several others.…”
Section: Discussionsupporting
confidence: 89%
“…al. 5 describes a process that requires a significant investment of clinical resources but also a significant improvement in resource utilization. With larger numbers of participants, it may be possible to achieve cost savings through economies of scale.…”
mentioning
confidence: 99%
“…Ten studies used a medical care plan intervention, three of which with added social supports (Gray-Eurom et al, 2015), disease management (Simpson et al, 2017), or community health workers (Lin et al, 2017). One of the 10 medical care plan evaluations did not report any tests of statistical significance.…”
Section: Resultsmentioning
confidence: 99%